Colonization of Raphanus sativus by human pathogenic microorganisms - Szymańska, Sonia; Deja-Sikora, Edyta; Sikora, Marcin; Niedojadło, Katarzyna; Mazur, Justyna; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2024)
Contamination of vegetables with human pathogenic microorganisms (HPMOs) is considered one of the most important problems in the food industry, as current nutritional guidelines include increased consumption of raw or minimally processed organic vegetables due to healthy lifestyle promotion. Vegetables are known to be potential vehicles for HPMOs and sources of disease outbreaks. In this study, we tested the susceptibility of radish (Raphanus sativus) to colonization by different HPMOs, including Escherichia coli PCM 2561, Salmonella enterica subsp. enterica PCM 2565, Listeria monocytogenes PCM 2191 and Bacillus cereus PCM 1948. We hypothesized that host plant roots containing bactericidal compounds are less prone to HPMO colonization than shoots and leaves. We also determined the effect of selected pathogens on radish growth to check host plant-microbe interactions.We found that one-week-old radish is susceptible to colonization by selected HPMOs, as the presence of the tested HPMOs was demonstrated in all organs of R. sativus. The differences were noticed two weeks after inoculation because B. cereus was most abundant in roots (log 10 CFU -2.54), S. enterica was observed exclusively in stems (log 10 CFU -3.15), and L. monocytogenes and E. coli were most abundant in leaves (log 10 CFU -4.80 and 3.23, respectively). The results suggest that E. coli and L. monocytogenes show a higher ability to colonize and move across the plant than B. cereus and S. enterica. Based on fluorescence in situ hybridization (FISH) and confocal laser scanning microscopy (CLSM) approach HPMOs were detected in extracellular matrix and in some individual cells of all analyzed organs. The presence of pathogens adversely affected the growth parameters of one-week-old R. sativus, especially leaf and stem fresh weight (decreased by 47-66% and 17%-57%, respectively). In two-week-old plants, no reduction in plant biomass development was noted. This observation may result from plant adaptation to biotic stress caused by the presence of HPMOs, but confirmation of this assumption is needed. Among the investigated HPMOs, L. monocytogenes turned out to be the pathogen that most intensively colonized the aboveground part of R. sativus and at the same time negatively affected the largest number of radish growth parameters.